PENGEMBANGAN MEDIA PEMBELAJARAN PETA BUDAYA BERBANTU APLIKASI STORYLINE 3 PADA PEMBELAJARAN TEMATIK DI KELAS IV SD - Mahliza Aulia Lubis; Sukmawarti Sukmawarti (Jurnal Inovasi Penelitian, 2023)
This study uses Research and Development methods to develop teaching materials in the form of learning links that contain thematic learning materials, namely cultural themes. This research and development aims to produce new products through the development process. Therefore, teaching materials that have been developed with all efforts are also expected to achieve maximum results. The process of developing teaching materials refers to the research and development process, including the steps that the author must take to achieve the research objectives. Based on research that has been carried out on the development of cultural maps learning media with the help of storyline 3 application in thematic learning in fourth grade elementary school, the author uses the 4D Development Model (Define, Design, Develov, and Disseminate.) verified by media validators, material validators, and learning validators, who have met the development stages. The results obtained from the student's test met the very good standard of 91.87%.